Child Feeding and Parenting Style Outcomes and Composite Score Measurement in the ‘Feeding Healthy Food to Kids Randomised Controlled Trial’ - Kerith Duncanson; Tracy L. Burrows; Clare E. Collins (Children, 2016)
Child feeding practices and parenting style each have an impact on child dietary intake, but it is unclear whether they influence each other or are amenable to change. The aims of this study were to measure child feeding and parenting styles in the Feeding Healthy Food to Kids (FHFK) Randomized Controlled Trial (RCT) and test a composite child feeding score and a composite parenting style score. Child feeding and parenting style data from 146 parent-child dyads (76 boys, aged 2.0–5.9 years) in the FHFK study were collected over a 12-month intervention. Parenting style was measured using parenting questions from the Longitudinal Study of Australian Children and the Child Feeding Questionnaire (CFQ) was used to measure child feeding practices. Data for both measures were collected at baseline, 3 and 12 months and then modelled to develop a composite child feeding score and a parenting score. Multivariate mixed effects linear regression was used to measure associations between variables over time. All child feeding domains from the CFQ were consistent between baseline and 12 months (p < 0.001), except for monitoring (0.12, p = 0.44). All parenting style domain scores were consistent over 12 months (p < 0.001), except for overprotection (0.22, p = 0.16). A significant correlation (r = 0.42, p < 0.0001) existed between child feeding score and parenting style score within the FHFK RCT. In conclusion, composite scores have potential applications in the analysis of relationships between child feeding and dietary or anthropometric data in intervention studies aimed at improving child feeding or parenting style. These applications have the potential to make a substantial contribution to the understanding of child feeding practices and parenting style, in relation to each other and to dietary intake and health outcomes amongst pre-school aged children.